Attainment of recommended therapeutic targets of modifiable cardiovascular risk factors among individuals with type 2 diabetes mellitus screened at a diabetes clinic in Sri Lanka - Weerarathna TP (Dove Medical Press, 2018)
Thilak Priyantha Weerarathna,1 Herath Mudiyanselage Meththananda Herath,1 Gayani Liyanage,1 Miyuru Kavinda Weerarathna,2 Vidarsha Senadheera2 1Faculty of Medicine, University of Ruhuna, Matara, Sri Lanka; 2Faculty of Medicine, University of Colombo, Colombo, Sri Lanka Introduction: Implementation of effective measures to control rising burden of cardiovascular diseases among patients with type 2 diabetes mellitus (T2DM) requires information on the adequacy of control and identification of specific groups with suboptimal control of blood glucose, lipids and blood pressure. Methods: A cross-sectional study of patients with T2DM referred from primary care to a diabetes center was carried out to estimate the proportion of patients achieving the recommended therapeutic targets of four major modifiable cardiovascular risk factors: glycosylated hemoglobin (HbA1c <7%), low-density lipoprotein cholesterol <100 mg/dL, systolic blood pressure (SBP) <130 mmHg and diastolic blood pressure (DBP) <80 mmHg and their associations with age, gender, duration of diabetes and body mass index were studied. Results: Mean (SD) age and the duration of the sample of 2422 (65% males) were 52 (11) and 9 (3), respectively. Percentages with optimal HbA1c, low-density lipoprotein cholesterol, SBP and DBP were 25.2%, 24.3%, 32% and 56.7%, respectively. Only 2% had achieved optimal control of all four risk factors. Significantly higher percentages of males were having optimal HbA1C, SBP and DBP, and regression analysis revealed that male gender was significantly associated with optimal control of SBP. Conclusion: Control of cardiovascular risk diseases factors among patients with T2DM managed in the primary care settings needs further improvements in target achievement in all four modifiable risk factors. Keywords: suboptimal control, therapeutic targets, type 2 diabetes mellitus, Sri Lanka